Perancangan Instrumen Tes Literasi Kimia Pada Materi Asam dan Basa - Ade Wahyuni; Eka Yusmaita (Edukimia, 2020)
Designing chemical literacy test instrumentation of acid and base topic is carried out to help develop student’s chemical literacy abilities that are beneficial to life. The purposed of this research is to describe the stages of designing questions using Model of Educational Reconstruction and describing the value of the content validity of chemical literacy questions on acid and base topic. The research’s type is to development with MER design. The content validity test conducted by 3 validates. The research instrument used was a question of chemical literacy in acid and base topic totaling 9 discourse questions which were elaborated in 15 item questions. The data obtained were processed using the Aiken’s V formula. The result showed that the instrument’s content validity considered as valid.